Sistem Informasi Membership Dan Pengaturan Jadwal Untuk Mempermudah Administrasi Pada Alto Myshouse Berbasis Web - Putra, Fransiskus Handika; Aditya, Addin; sakaria, setiabudi (J-INTECH (Journal of Information and Technology), 2022)
In this study writers will design a safer and more efficient membership information system at alto myshouse fitness center. At present alto myshouse still use a manual membership system in which their members fill out membership forms using paper media that is then stored. This system has many flaws like member data can easily disappear or malfunction. Therefore, compl erasing web-based membership information systems that will assist security and efficiency in locating member data and also to simplify the application process, a system that can systematize registration systems for members, instructors and schedules is included in the database. So that system users get their desired information quickly and accurately. Therefore, the membership information system design based on the website is made accessible to members. To design this website based membership information system collecting the necessary data through direct observation and interview with admin of alto myshouse. The program is then made to use PHP as programming language and mysql for database storage. The major stage of system design includes analysis of the requirements of software, system design, coding, testing, implementation and maintenance of programs created. This web-based information system will be able to improve current system weaknesses.